Kreativitas Mengajar Mahasiswa PPL II Jurusan PGMI Fakultas Tarbiyah dan Keguruan UIN Antasari Banjarmasin Tahun 2015/2016 - Shalihah, Siti (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2018)
The study aims to determine the creativity of teaching students PPL II PGMI FTK UIN Antasari Year 2015/2016 and the factors that influence it. This type of research is field research (field research) with qualitative approach. The design used in this research is descriptive research. Objects in this research is the creativity of teaching students PPL II Faculty of Tarbiyah and Teacher Training Program PGMI Antasari Banjarmasin Year Ajisi 2015/2016. Subjects in this study were Students PPL II force 2012 Department of PGMI Faculty of Tarbiyah and Teacher Training UIN Antasari Banjarmasin located in MI Al Istiqamah, amounting to ten people. Techniques of data collection using observation, interviews, and documentation. Data analysis technique used is descriptive qualitative. The result of the research shows that the creativity of teaching students of PPL II UIN can be seen from the variation of active learning strategy and the variation of media used. While for the source of learning, PPL II students are still many who only use learning resources in the form of textbooks. Factors that affect the creativity of teaching students PPL II, including teacher candidate factors consisting of educational background and learning experience, facilities and learning resources, as well as conductive environmental conditions.